ASSESSMENT TECHNIQUES ADMINISTERED IN ENGLISH LANGUAGE CLASSROOM FOR YOUNG LEARNERS: A Descriptive Research Conducted in Primary Schools in Bandung Kulon - Siti Masitoh, - (2008)
Assessment for young learners has been considered important in English language classroom. This research investigated assessment techniques, aspects assessed, and reasons of choosing those assessment techniques for young learners. Descriptive method was applied in this research to give portrayal of the phenomena without manipulation. The data obtained were from document analysis and interviews of three respondents in two selected primary schools in Bandung Kulon. Having collected the data, theories of Georgiou (2003) and Heaton (1995) were employed to analyze aspects assessed. The findings showed that the teachers mainly used traditional tests because of their practicality of setting and scoring. Other assessment techniques employed to get a reliable picture of students' progress were oral tests, take-home tasks, and observation. , In terms of aspects assessed, linguistics aspects mostly assessed in traditional tests, oral tests, and take-home tasks. Compared to linguistic aspects, non-linguistics aspects were assessed through observation. In conclusions, the teachers seemed to have inadequate knowledge and ability to implement assessment techniques in their classroom. It also seemed the teachers do not have access to achieve information dealing with the assessment used. The aspects assessed and assessment techniques used were likely influenced by the teacher's knowledge. Hence, the teachers are expected to expand their knowledge through attending seminar and training as one of the suggestions.